Hepatitis C From Infection to Cure - Shahid, Imran (IntechOpen, 2018)
The propagation of hepatitis C from acute to chronic infection and afterward to end-stage liver diseases (hepatic fibrosis, cirrhosis, and hepatocellular carcinoma) involves a highly orchestrated series of molecular and cellular events, including a plethora of genes and cell signaling cascades. The treatment paradigms was revolutionized after the development and approval of all oral interferon-free direct-acting antivirals achieving higher sustained virologic response rates in treated individuals. This book pragmatically overviews the intricate interplay between viral and host factors during hepatitis C virus infection progression, as well as other hepatitis C-associated clinical implications. Hepatitis C - From Infection to Cure also provides up-to-date information about hepatitis C cures for clinicians, physicians, and healthcare providers with an ample understanding of the current treatment horizon, as well as other investigational and emerging treatment strategies. The authors with their valuable scientific contributions belong to many eminent institutes around the world and are much experienced in hepatitis C virology, pathology, and therapeutics.